2000
DOI: 10.1088/0953-8984/12/41/301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repulsive and attractive interactions in the adsorption of confined polydisperse fluids

Abstract: A density functional perturbative approximation, which is based on the pair distribution function, has been developed to investigate the influence of attractive and repulsive interactions on the density behaviour of a confined polydisperse fluid. The calculated result shows that the attractive and repulsive interactions in the model potential are strongly affected on the adsorption of a confined polydisperse fluid as well as the cavity size and particle size ratio. The attractive interaction in a polydisperse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Obviously, higher porosity lowers matrix-fluid correlations. Moreover, polydispersity of the porous medium also causes smoothing of the correlation function-previous calculations carried out for uniform, 32,33,36 as well as for nonuniform fluids 35,37,38 indicated that the structure of a polydisperse fluid is less pronounced than the structure of a monodisperse fluid having the same total density. Figures 4͑b͒ and 4͑c͒ also show the correlation functions between templates ͑''empty sites'' of a given size͒ and fluid particles.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, higher porosity lowers matrix-fluid correlations. Moreover, polydispersity of the porous medium also causes smoothing of the correlation function-previous calculations carried out for uniform, 32,33,36 as well as for nonuniform fluids 35,37,38 indicated that the structure of a polydisperse fluid is less pronounced than the structure of a monodisperse fluid having the same total density. Figures 4͑b͒ and 4͑c͒ also show the correlation functions between templates ͑''empty sites'' of a given size͒ and fluid particles.…”
Section: Resultsmentioning
confidence: 99%
“…V av (a), If the FMT expressions ((B6)È(B8)) for the one-particle direct correlation functions are substituted into eqn. (14), c a (1) one obtains a set of highly non-linear and non-local equations for the unknown density proÐles, which must be solved iteratively, for any given set of chemical potentials subject to Mk a N, the boundary conditions (10) or (11). This is achieved on a Ðne 1d grid, using a Picard iterative procedure,23 which must be repeated for each composition of the bulk mixture, i.e.…”
Section: Density Functional Theory and Simulationsmentioning
confidence: 99%
“…The actual density of interacting spheres is given by eqn. (14), where is a negative function of r for hard sphere c a…”
Section: Gpmentioning
confidence: 99%
See 1 more Smart Citation
“…Pagonabarraga et al [32] extended fundamental measures' theory to polydisperse hard-sphere fluids. This, and similar approaches were subsequently applied to investigate various confined polydisperse colloidal systems such as hard walls or idealized semipermeable membranes [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%